Studies on selected physiological and biochemical parameters responsible for resistance to spot blotch of barley (Hordeum vulgare L.) - Kumar, Pradeep; Kalappanavar, I K; Arunkumar, G S; Pradeep, P E (Journal of Cereal Research, 2011)
The spot blotch caused by Helminthosporium sativum Pam., King and Bakke is attaining importance in Karnataka andNorthern and Eastern parts of India, Hence, an attempt was made for a systematic study of the various physiologicaland biochemical factors which contribue to the resistance of the barley genotypes, The resistant genotypes recordedless number of stomata, lesser length and breadth of the stomata when compared to susceptible genotypes. Thehistological studies indicated that the cuticular thickness, epidermal thickness were more in resistant genotypes thanin susceptible ones. The resistant genotypes recorded less number of epidermal cells per millimeter (mm) comparedto susceptible ones. From the biochemical studies, it has indicated that resistant genotypes had more amount of totalsugar, reducing sugar protein, total phenols, amino acid and wax content than susceptible genotypes. These weredecreased after infection and the decrease was more in susceptible genotypes than in resistant ones. In contrast tothis non-reducing sugars were more in susceptible genotypes than in resistant ones.